Manifestation of osteoblastic phenotypes in the sarcomatous component of epithelial carcinoma and sarcomatoid carcinoma. Issue 6 (June 2017) - Takashima, Yasutoshi; Murakami, Teppei; Inoue, Takao; Hagiyama, Man; Yoneshige, Azusa; Nishimura, Syunji; Akagi, Masao; Ito, Akihiko
Epithelial carcinomas occasionally have sarcomatous components that consist primarily of spindle and cuboidal cells, which often resemble osteoblasts. Sarcomatoid carcinomas consist of similar cells. Recent studies have characterized these phenomena as a manifestation of epithelial–mesenchymal transition in carcinoma cells, but the mesenchymal phenotypes that manifest in sarcomatous cells of epithelial carcinomas are not well understood. Here, we examined the expression profiles of four osteoblastic differentiation biomarkers in the sarcomatous components of multiple carcinoma types, including five renal clear cell, four breast invasive ductal, two esophageal, one maxillary squamous cell, three larynx, three lung, one liver, and one skin sarcomatoid carcinoma. Expression was analyzed by immunohistochemistry using antibodies against cell adhesion molecule 1, a member of the IgCAM superfamily, osterix transcription factor (Osterix), cluster of differentiation 151, a transmembrane 4 superfamily member, and alkaline phosphatase. Immunostaining intensity was rated in scale 0 (negative), 0.5 (weak), and 1 (strong) for each marker, and the four scale values were summed to calculate osteoblastic scores. In all, 10 cases had a osteoblastic score ≥3, and all of these 10 cases were cell adhesion molecule 1- and Osterix-positive. Eight and five of the nine samples with a osteoblastic score <3 were negative for cell adhesion molecule 1 ( p < 0.0001) and Osterix ( p = 0.006), respectively. The other markers showed no statistical significance. These results indicate that osteoblastic differentiation can occur in carcinoma cells and that cell adhesion molecule 1 could be a useful marker for identifying this phenomenon in carcinoma tissues.